Influence of a carbon-based tribofilm induced by the friction temperature on the tribological properties of impregnated graphite sliding against a cemented carbide - Jun Zhao; Qingzhan Li; Shuangxi Li; Shicong Li; Guangyan Chen; Xinghua Liu; Yongyong He; Jianbin Luo (Friction)
Abstract Impregnated graphite has attracted considerable attention and has been widely used as an ideal friction material in many fields. However, the influence of the friction temperature on its tribological properties has not been clearly studied; furthermore, the evolution mechanism of transferred tribofilm is unknown. In this study, the tribological properties of impregnated graphite were investigated at different friction temperatures, and the evolution of the carbon-based tribofilm was also determined. The results revealed that the tribological properties significantly improved with an increase in friction temperature. The friction coefficient and wear depth of impregnated graphite reduced by 68% and 75%, respectively, at a high temperature of 160 °C compared with those of non-impregnated graphite. The significant properties of the impregnated graphite can be attributed to a transferred carbon-based tribofilm with an ordered structure induced by the friction temperature, which uniformly and stably adsorbs on friction interfaces. This study provides an important basis for designing graphite-based friction materials with improved properties suited for industrial applications.